(untitled) (Ideoscopio, 2026)
Writing a letter is not only not common nowadays, it is still a hard thing to do, even harder when you do it to a loved one. This letter, born from an English midterm exam, proposes a simple yet powerful metaphor of what a mother may mean to a daughter.